Financing MSME Using Analysis of IFAS and EFAS Matrix: Case Study in Honey Pumpkin Business - Hidayah, Islamiati; Abadi, M. Kurnia Rahman; Falach, Ghulam; Ismail, Moh (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2024)
This study is aimed to find out how the Honey Pumpkin business development strategy is carried out by Honey Pumpkin Farmers in Banyusokah Village, Sampang Regency based on EFAS and IFAS Matrix. The method employed in this study is descriptive qualitative which is aims to describe, describe, record, and analyze existing and current conditions. The result of the study showed that Honey Pumpkin business in Banyoksah Village of Sampang Regency is able to implement the growth oriented strategy for developing its business. The suggested strategies are firstly, to distribute the products in the store at Sampang Regency and utilizing social media such as IG, whatsApp and so on for marketing. Secondly, diverging the processed product from honey pumpkin and turning customer into reseller. Thirdly, replacement of production technology used with more sophisticated and modern to increase the production effectively and efficiently. Lastly, opening several branch of store that owned by the company. Meanwhile, financing aspect regarding to growth oriented strategy several financing model could be useful. For example, working capital loan, digital marketing loan, business expansion loan, and equipment loans or leasing arrangement. Therefore, research and approach of financial institutions, banks, and alternative lenders is necessary to explore specific financing options that suit with growth strategies.